Integrality and higher education aimed at the Brazilian Unified Health System from the perspective of physical therapy undergraduate students - Samira Mendonça de Almeida; Alberto Mesaque Martins; Patrícia Maria Fonseca Escalda (Universidade de São Paulo, 2014)
In recent years, there has been the need to reorganize the curriculum of undergraduate courses in the health science field in order to educate professionals to be able to practice the principles of the Brazilian Unified Health System from the perspective of integrality. From a qualitative research perspective, this study aimed to identify the perceptions and opinions of physical therapy undergraduate students regarding comprehensive health care and about the principle of comprehensive health care in their education. Three focus groups were conducted with students in their senior year of the undergraduate course in physical therapy enrolled in three universities in the Federal District. After analyzing the content, results show that despite government efforts and changes in the curriculum proposals, it was observed that undergraduate education in physical therapy still does not favor the Brazilian Unified Health System and its guiding principles, in particular comprehensive health care. It is necessary to invest in reflective spaces that articulate university (faculty and students), health services, management authorities, municipal policies and social movements in order to yield new teaching and learning possibilities that will contribute to the transformation of the university education aimed at the Brazilian Health System.